Anthracycline-related cardiotoxicity in older patients with acute myeloid leukemia: a Young SIOG review paper - Neuendorff, Nina Rosa; Loh, Kah Poh; Mims, Alice S.; Christofyllakis, Konstantinos; Soo, Wee-Kheng; Bölükbasi, Bediha; Oñoro-Algar, Carlos; Hundley, William G.; Klepin, Heidi D. (Blood advances, 2020)
Abstract: The incidence of acute myeloid leukemia (AML) increases with age. Intensive induction chemotherapy containing cytarabine and an anthracycline has been part of the upfront and salvage treatment of AML for decades. Anthracyclines are associated with a significant risk of cardiotoxicity (especially anthracycline-related left ventricular dysfunction [ARLVD]). In the older adult population, the higher prevalence of cardiac comorbidities and risk factors may further increase the risk of ARLVD. In this article of the Young International Society of Geriatric Oncology group, we review the prevalence of ARLVD in patients with AML and factors predisposing to ARLVD, focusing on older adults when possible. In addition, we review the assessment of cardiac function and management of ARLVD during and after treatment. It is worth noting that only a minority of clinical trials focus on alternative treatment strategies in patients with mildly declined left ventricular ejection fraction or at a high risk for ARLVD. The limited evidence for preventive strategies to ameliorate ARLVD and alternative strategies to anthracycline use in the setting of cardiac comorbidities are discussed. Based on extrapolation of findings from younger adults and nonrandomized trials, we recommend a comprehensive baseline evaluation of cardiac function by imaging, cardiac risk factors, and symptoms to risk stratify for ARLVD. Anthracyclines remain an appropriate choice for induction although careful risk-stratification based on cardiac disease, risk factors, and predicted chemotherapy-response are warranted. In case of declined left ventricular ejection fraction, alternative strategies should be considered.